PENGAKUAN NEGARA TERHADAP HAK-HAK POLITIK (RIGHT TO VOTE) MASYARAKAT ADAT DALAM PELAKSANAAN PEMILIHAN UMUM (Studi Putusan Mahkamah Konstitusi No.47-81/PHPU.A-VII/2009) - Zazili, Ahmad (Jurnal Konstitusi, 2012)
Constitutional right is basic right for all Indonesian people, not least for indigenous people which still uphold the values of their customary law. Customary law is often  different  from  the  positive  law  in  Indonesia,  but it’s not a reason to deny the customary law on  indigenous  people  in  a region. One of the Indigenous people is in Yahukimo where the community uses their customary law in various patterns of life. Therefore, even in the election they use their own customary law and are not  guided  by  the  Election Law. Noken is the way they cast a vote. Constitutionality of Noken is accepted as a cultural value by the Constitutional Court.